Managing Weeds In Dry Direct Seeded Rice: A Profound Challenge - Gyawaly, Pankaj; Sah, Shrawan Kumar; Bhattarai, Rajendra Kumar; Chaulagain, Bhimsen; Pantha, P. (Agronomy Journal of Nepal, 2021)
Dry Direct Seeded Rice (DDSR) is a promising technology to address environmental, water, labor and profitability issue that is constantly threatening the rice farming community around the world. Rice yield under DDSR is primarily limited due to weeds. There are instances of complete crop failure in DDSR owing to poorly managed weeds. More than 50 weeds species infest DDSR crop due to aerobic nature of soil confronting a major challenge in the wide spread adoption of dry direct seeding. Direct-seeded rice faces a potential threat from changes in the competing weed flora, with an increase in those species that are difficult to control. This review article presents the prospects of DDSR along with the available weed management strategies such as preventive, physical, chemical, cultural and biological methods and their judicious use. Over reliance on only one approach of managing weeds may be back firing as well. The use of chemical means are getting popular in an alarming rate for being cost effective, without calculating the environmental concerns which might lead to herbicidal resistance and negative consequences to environment and human health. Therefore, it is necessary to understand the environment while shifting from transplanted rice to dry direct seeding, identifying weeds flora and choosing or integrating the best weed management practices foreseeing the future consequences. The logical integration of available weed management options that is ecologically sound, economic and effective for season long weed control is the main essence that ensures the sustainability of rice production.